Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.

Select all of the following that are ordered pairs of the given function.

[tex]\[ f(x) = 3 - 2x \][/tex]

A. [tex]\((-2, -1)\)[/tex]

B. [tex]\((1, 0)\)[/tex]

C. [tex]\((2, -1)\)[/tex]

D. [tex]\((0, 3)\)[/tex]

E. [tex]\((-1, 5)\)[/tex]


Sagot :

To determine if an ordered pair [tex]\((x, y)\)[/tex] is a solution to the function [tex]\( f(x) = 3 - 2x \)[/tex], we need to check if substituting [tex]\( x \)[/tex] into the function [tex]\( f(x) \)[/tex] results in the value [tex]\( y \)[/tex].

Let's evaluate each of the given ordered pairs against the function [tex]\( f(x) = 3 - 2x \)[/tex]:

1. [tex]\((-2, -1)\)[/tex]:
- Substitute [tex]\( x = -2 \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(-2) = 3 - 2(-2) = 3 + 4 = 7 \][/tex]
- The result is [tex]\( 7 \)[/tex], not [tex]\(-1\)[/tex]. Therefore, [tex]\((-2, -1)\)[/tex] is not a solution to the function.

2. [tex]\((1, 0)\)[/tex]:
- Substitute [tex]\( x = 1 \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(1) = 3 - 2(1) = 3 - 2 = 1 \][/tex]
- The result is [tex]\( 1 \)[/tex], not [tex]\( 0\)[/tex]. Therefore, [tex]\((1, 0)\)[/tex] is not a solution to the function.

3. [tex]\((2, -1)\)[/tex]:
- Substitute [tex]\( x = 2 \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(2) = 3 - 2(2) = 3 - 4 = -1 \][/tex]
- The result is [tex]\(-1\)[/tex], which matches [tex]\( y \)[/tex]. Therefore, [tex]\((2, -1)\)[/tex] is a solution to the function.

4. [tex]\((0, 3)\)[/tex]:
- Substitute [tex]\( x = 0 \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(0) = 3 - 2(0) = 3 - 0 = 3 \][/tex]
- The result is [tex]\( 3 \)[/tex], which matches [tex]\( y \)[/tex]. Therefore, [tex]\((0, 3)\)[/tex] is a solution to the function.

5. [tex]\((-1, 5)\)[/tex]:
- Substitute [tex]\( x = -1 \)[/tex] into [tex]\( f(x) \)[/tex]:
[tex]\[ f(-1) = 3 - 2(-1) = 3 + 2 = 5 \][/tex]
- The result is [tex]\( 5 \)[/tex], which matches [tex]\( y \)[/tex]. Therefore, [tex]\((-1, 5)\)[/tex] is a solution to the function.

Hence, the ordered pairs that are solutions to the function [tex]\( f(x) = 3 - 2x \)[/tex] are:
- [tex]\((2, -1)\)[/tex]
- [tex]\((0, 3)\)[/tex]
- [tex]\((-1, 5)\)[/tex]

The selected ordered pairs that satisfy the function are [tex]\((2, -1)\)[/tex], [tex]\((0, 3)\)[/tex], and [tex]\((-1, 5)\)[/tex].